Thermal Comfort Study of a Building Equipped with Thermoelectric Air Duct System for Tropical Climate - Kashif, Irshad; Khairul, Habib; F., Basrawi; Nagarajan, Thirumalaiswamy; R., Saidur; Bidyut, Baran Saha (Elsevier Ltd, 2015)
This paper examined the performance of a thermo-electric air duct system (TE-AD), which employs the thermo-electric module (TEMs) inside an air duct for providing thermal comfort in Malaysian environment. Twenty human subjects were exposed to test room equipped with TE-AD system operating at six different input current supply from 2 A to 7 A. Both objective and subjective measurements were carried out. Results show that with the increment of input current supply to the TE-AD system, subject's thermal response related to indoor condition of test room shifted from warm to neutral. Optimum performance of the TE-AD system was obtained at the input current supply of 6 A, more than 80% of subjects responded in the range of ±1 and meets ASHARE standards of acceptability criteria. Further increase in input current supply deteriorates the cooling performance of the TE-AD system. Economic comparison of the TE-AD system with the existing air conditioning system shows that economic saving of US$ 127.34/year can be achieved with additional benefits of Freon free, convenient installation, no moving part and reliable operation.